Design + Organization Development: Three Steps on the Bridge to the Other Side. (2nd November 2015) - Dunne, Alex M.; Peck, Tonya M.
Abstract : These organization development specialists offer some ways to make your staff meetings and meetings with clients more interesting, more inclusive, and more productive. You can start the process by taking out some chairs and leaving out the PowerPoint presentation. In which we learn something about organization development, and how to run a meeting that isn't filled with bored people staring at their laptops.